Prospective Control Systems and Cyber-Securities for Electrical Secondary Substations - Jidin R.; Basir Khan M.R.; Jamil N.; Al-Bahadly I. (Institute of Electrical and Electronics Engineers Inc., 2023)
Authentication; Control systems; Cryptography; Electric utilities; Electric vehicles; Network security; Autonomous operations; Cryptographic algorithms; Electricity distribution networks; End-user participations; Energy landscape; Integration of renewable energies; Multiple stakeholders; Voltage disturbances; Peer to peer networks